2014
DOI: 10.7903/ijcse.1149
|View full text |Cite
|
Sign up to set email alerts
|

Schools and Cyberbullying: Problem Perception, Current Actions and Future Needs

Abstract: Cyberbullying is a common phenomenon amongst young people. It exhibits many similarities to traditional school bullying, with a potentially serious impact on the mental health and school functioning of victims. For this reason, action by schools is often recommended. The aim of this article is to provide a better picture of what schools are currently doing to address cyberbullying and of what schools will need to continue doing so in the future. An online survey was conducted among staff members of 309 primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
9
0
4
Order By: Relevance
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
“…Educators have reported difficulty in responding to bullying incidents that they did not witness (Mishna, Pepler, & Wiener, 2006). Similarly, although many educators are aware of cyberbullying, few take steps to address it and many are uncertain about how to confront cyberbullying, which often occurs outside of school (Cassidy, Brown, & Jackson, 2012; Stauffer, Heath, Coyne, & Ferrin, 2012; Vandebosch, Poels, & Deboutte, 2014). Nonetheless, educators can address cyberbullying occurring on or off school grounds if the aggression creates a hostile school environment and substantially disrupts a student’s learning environment (Stuart-Cassel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The scarce studies available on school educator practices against cyberbullying found that despite high problem awareness, few school educators took action and most were unsure what to do (Akbulut & Çuhadar, 2011;Cassidy, Brown, & Jackson, 2012;Eden, Heiman, & Olenik-Shemesh, 2013;Huang & Chou, 2013;Li, 2008;Stauffer, Heath, Coyne, & Ferrin, 2012;Vandebosch, Poels, & Deboutte, 2014). Female educators recognized more harm related to cyberbullying than male educators (Eden et al, 2013).…”
Section: School Educator Practices and Perceptions Towards Cyberbullyingmentioning
confidence: 99%